The international law of the sea - Rothwell, Donald 1959-; Stephens, Tim (Law teacher) (Hart Publishing Ltd., 2016)
The law of the sea provides for the regulation, management and governance of the ocean spaces that cover over two-thirds of the Earth's surface. This book provides a contemporary explanation of the foundational principles of the law of the sea, a critical overview of the 1982 United Nations Convention on the Law of the Sea and an analysis of subsequent developments including the many bilateral, regional and global agreements that supplement the Convention